A Technique for Better Energy Management of Single-Stage Topology of Stand-Alone Photovoltaic System - Abbas, Ghulam; Azeem, Omar; Murtaza, Ali Faisal; Tahir, Umair (International Journal of Integrated Engineering, 2020)
This paper proposes a technique for energy managing of a stand-alone photovoltaic system. The proposed system employs a power processing inverter, which contains high PV voltage at the input to mitigate the magnitude of AC signal at the output, eliminating use of DC-DC converter and reduces the input capacitor size of PV array. To meet the power requirement of load and to maintain the maximum power point operation of PV array, battery bank is utilized with a bi-directional converter. An impedance model of the complete system is executed. Based on the model, the control architecture is designed which works in four modes: 1)  if load demands >  MPP of PV, additional current is extracted from the battery; 2) if load demands